Add-on clinical effects of simvastatin and ondansetron in patients with schizophrenia stabilized on antipsychotic treatment: pilot study. (June 2014) - Chaudhry, Imran B.; Husain, Nusrat; Drake, Richard; Dunn, Graham; Husain, M. Omair; Kazmi, Ajmal; Hamirani, Munir M.; Rahman, Raza; Stirling, John; Deakin, William
Objectives: There is some evidence that anti-inflammatory treatment may have beneficial effects in schizophrenia and major depression. Statins are cholesterol-lowering agents but have been found to be anti-inflammatory and also decrease C-reactive protein (CRP). Ondansetron is a serotonin (5-HT3) receptor antagonist widely used to prevent nausea and vomiting in patients receiving chemotherapy for cancer. Small studies have suggested that adjunctive ondansetron is efficacious against schizophrenia symptoms. We carried out a feasibility study in schizophrenia patients (within 5 years of first diagnosis) to explore the adjunctive use of simvastatin and ondansetron on positive, negative and general psychopathology. Methods: This was a 12-week rater-blind placebo-controlled study. A total of 36 patients with DSM-IV diagnosis of schizophrenia were recruited, 12 in each arm. Patients were assessed at baseline and at 12 weeks using Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression (CGI) scale, Global Assessment of Functioning (GAF) and Abnormal Involuntary Movement Scale (AIMS). Results: Both simvastatin and ondansetron provide some evidence of a reduction in symptoms compared with treatment as usual (TAU) on PANSS total score, although this was not statistically significant. In the secondary analyses, no significant differences were seen on CGI, GAF and AIMS. Conclusions: Anti-inflammatory treatments have been shown to have some beneficial effects in schizophrenia. Both simvastatin and ondansetron provide some evidence of a reduction in symptoms compared with TAU. This study has led to a larger Stanley Medical Research Institute (SMRI)-funded, double-blind, randomized control trial.